Genetic diversity of Nipah virus in Bangladesh. (January 2021) - Rahman, M.Z.; Islam, M.M.; Hossain, M.E.; Rahman, M.M.; Islam, A.; Siddika, A.; Hossain, M.S.S.; Sultana, S.; Islam, A.; Rahman, M.; Rahman, M.; Klena, J.D.; et al.
Highlights: The study added information about the genetic diversity and molecular characterization of Nipah virus (NiV) strains, both from bats and humans in Bangladesh. This study provides molecular and methodological information for the early detection of NiV in the environmental samples to assess its epidemic potential in humans. It will also help in understanding the ecology of NiV. The study revealed that the strains of NiV have been continuously evolving and NiV-BD genotype diverged from its ancestral during 1995 and formed two sublineages, NiV-BD 1 and 2. The occurrence of any particular sublineage of NiV strains was not limited to a specific outbreak region. Abstract: Background: Nipah virus (NiV) infection, often fatal in humans, is primarily transmitted in Bangladesh through the consumption of date palm sap contaminated by Pteropus bats. Person-to-person transmission is also common and increases the concern of large outbreaks. This study aimed to characterize the molecular epidemiology, phylogenetic relationship, and the evolution of the nucleocapsid gene (N gene) of NiV. Methods: We conducted molecular detection, genetic characterization, and Bayesian time-scale evolution analyses of NiV using pooled Pteropid bat roost urine samples from an outbreak area in 2012 and archived RNA samples from NiV case patients identified during 2012–2018 in Bangladesh. Results: NiV-RNA was detected in 19% (38/456) of bat roost urine samples and among them; nine N gene sequences were recovered. We also retrieved sequences from 53% (21 out of 39) of archived RNA samples from patients. Phylogenetic analysis revealed that all Bangladeshi strains belonged to NiV-BD genotype and had an evolutionary rate of 4.64 × 10 −4 substitutions/site/year. The analyses suggested that the strains of NiV-BD genotype diverged during 1995 and formed two sublineages. Conclusion: This analysis provides further evidence that the NiV strains of the Malaysian and Bangladesh genotypes diverged recently and continue to evolve. More extensive surveillance of NiV in bats and human will be helpful to explore strain diversity and virulence potential to infect humans through direct or person-to-person virus transmission.